Single-cell protein as an alternative protein source in feed for juvenile sea cucumber - Jiayin Zhang; Ning Chen; Yongcui Sha; Shanfei Fu; Chao Li; Qiang Xu; Fei Gao; Haiqing Wang (Aquaculture Reports)
Single-cell protein (SCP) has a nutritional profile that is comparable to most conventional protein sources, and can be produced with a lower environmental footprint. Finding alternative and palatable protein sources for juvenile sea cucumber feed may address the issue of slow growth during this stage. To assess the efficiency of SCP as an alternative protein source for juvenile sea cucumbers Stichopus monotuberculatus, a study was conducted with five levels of single-cell protein replacement in the feed (0 %, 10 %, 15 %, 20 %, and 25 %) to evaluate its effects on growth performance, biochemical composition, digestive and immune enzyme activities. The results revealed that the optimal 15 % replacement of single-cell protein in the diet significantly improved the growth performance of S. monotuberculatus. This could be attributed to the enhanced immune enzyme activities resulting from the inclusion of single-cell protein, with the 15 % treatment showing the most significant increase in these values. The amino acid composition was similar across the treatments, but the ratio of essential amino acids increased with inclusion of single-cell protein. As the single-cell protein inclusion increased, the levels of polyunsaturated fatty acids, such as C18:2n-6, C20:2n-6, C20:4n-6 and C20:5n-3 also increased, especially C20:4n-6 and C20:5n-3. Similar to the control, the replacement with single-cell protein did not have adverse effects on the activities of pepsin, trypsin, and lipase. In conclusion, single-cell protein has positive impacts on the growth, feed conversion rate, the biochemical composition of S. monotuberculatus and its immune capacity, which indicates that the single-cell protein has the potential to replace fishmeal as a new effective protein for sea cucumber. We concluded that this SCP can be as a sustainable substitute, capable of replacing 15 % of protein in the diet of juvenile sea cucumber, positively promoting their performance.